Educational Media and Technology Yearbook Volume 41 - Branch, Robert Maribe; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The Educational Media and Technology Yearbook has become a standard reference in many libraries and professional collections. It provides a valuable historical record of current ideas and developments in the field. Part One of this updated volume, (3z(BTrends and Issues in Learning, Design, and Technology,(3y (Bpresents an array of chapters that develop some of the current themes listed above, in addition to others. In Part Two, (3z(BLeadership Profiles,(3y (Bauthors provide biographical sketches of the careers of instructional technology leaders. Part Three, (3z(BOrganizations and Associations in North America,(3y (Band Part Four, (3z(BGraduate Programs,(3y (Bare, respectively, directories of instructional technology-related organizations and institutions of higher learning offering degrees in related fields. Finally, Part Five, the (3z(BMediagraphy,(3y (Bpresents an annotated listing of selected current publications related to the field.s
Preface -- Part I -- Introduction -- Issues and Trends in Instructional Technology: Increased Use of Mobile Technologies and Digital Content to Provide Un-Tethered Access to Training and Learning Opportunities -- Collaborative design of ICT-rich early literacy learning material: Design talk in teacher teams -- Social learning in a distributed environment: Lessons learned from online design education -- Understanding Help-Seeking Behavior of Students$1 (Bin a Flipped Classroom: A Structural Equation Modeling Approach -- Digging Deep into Communities of Inquiry at Purdue -- Real-time mutual gaze perception enhances collaborative learning and collaboration quality -- Critical Thinking in the Field of Educational Technology: Approaches, Projects, and Challenges -- Exploring the Cultural Dimensions of Learning: Models, Instruments, and Future Studies -- Part II -- Introduction -- Profile of Edward Caffarella -- Profile of Sharon Smaldino -- Part III -- Introduction -- Worldwide List of Organizations in Learning, Design, Technology, Information or Libraries -- Part IV -- Introduction -- Worldwide List of Graduate Programs in Learning, Design, Technology, Information or Libraries -- Part V -- Introduction -- Mediagraphy.s
Keywords: Education; Literacy; Educational Technology; Learning & Instruction; Literacy